The Influence Of Digital Marketing And Service Quality On Patient Satisfaction At RSUD Dr. Mohamad Soewandhie With Brand Experience As A Mediating Variable - Ariyanto Setyoaji; Sengguruh Nilowardono (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the influence of digital marketing and service quality on patient satisfaction at RSUD dr. Mohamad Soewandhie Surabaya, with brand experience as a mediating variable. Using a quantitative approach with a survey method, data were collected through questionnaires distributed to patients who have interacted with the hospital’s digital platforms. The results show that digital marketing significantly influences brand experience and patient satisfaction, with a strong mediation effect through brand experience. On the other hand, service quality has no significant effect on these two variables. This study emphasizes that digital marketing, through a positive brand experience, is the primary factor in enhancing patient satisfaction, while traditional service quality loses its relevance in the context of healthcare digitalization.